Ben Cousins and the ‘double life’: exploring citizenship and the voluntarity/compulsivity binary through the experiences of a ‘drug addicted’ elite athlete - Seear, K.; Fraser, Suzanne (Routledge, 2010)
Contemporary neo-liberal public health discourse is increasingly drawn to the language of 'addiction'. Disease models of addiction are mobilised to account for an expanding array of problematised activities, from the familiar smoking and drinking to newer candidates, such as overeating and gambling. Most models of addiction, including disease models, are underpinned by the idea that, unlike proper citizens of neo-liberal democracies, 'addicts' lack free will or agency. This lack can be attributed to any number of problems or dysfunctions: genetic, neurological, social or moral. One high-profile case, which challenges this approach to addiction, involves the famous Australian Rules football player Ben Cousins, one of Australia's most recognised and accomplished athletes. A highly decorated player in the Australian Football League (AFL), Cousins has publicly declared himself a 'drug addict'. In this article, we present an abridged version of an interview we conducted with Cousins around the end of his first season back in the sport (late 2009) following suspension by the AFL for 'bringing the game into disrepute'. In the interview, we explore Cousins' own understanding of drug 'addiction' and its relation to its apparent antithesis sporting prowess. We also examine the ramifications of the ostensible paradox between drug 'addiction' and sporting accomplishment for understandings of 'addiction' as compulsivity and lack of free will. Drawing on the work of the cultural studies theorist Sedgwick (1993), we identify in Cousins' own understandings of his drug 'addiction' a resistance to the absolute polarisation of voluntarity and compulsivity underpinning some of the most influential versions of the disease model of addiction. We discuss the implications of this polarisation, and of forms of resistance to it, for public health policies regarding drug addiction, and for the intersection of drug use and citizenship. Thinking through Sedgwick's alternative notion of 'habit', we reconsider concepts of addiction, briefly drawing in other phenomena also increasingly framed as 'epidemics of the will'.